La alimentación saludable para el desarrollo de la atención en niños de 4 años en el Centro de Educación Infantil Safari Kids, Ciudad de Riobamba. - Bravo Garabi, Blanca María (2024)
The main objective of this research is to determine the importance of healthy eating for the optimal development of care in 4-year-old children at the Safari Kids Early Childhood Education Center in the city of Riobamba. Methodologically, it comprises a qualitative and quantitative approach, that is to say, a mixed approach that integrates the review of bibliographic sources, to obtain the understanding of the topic, the modality is of field; the type of research is descriptive and the population is 22 children and 22 parents of the initial level 2, the applied technique is the survey and the instrument is a questionnaire, which has 12 closed questions addressed to the parents. A class was also given to the children, the activity is called "Mini Chefs", where they recognize what healthy foods are and how important it is for their academic performance. According to the results obtained it was possible to identify that food influences the development of children's attention, therefore, through the results of the survey we seek to raise awareness among parents to promote healthy eating habits in their homes on a daily basis so that their children can have a comprehensive development